Strengthening the Character Profile of Pancasila Students through Physical Education Learning - Qisthina Khoerunnisa Safwah; Tedi Supriyadi; Muhammad Nur Alif (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This study aims to analyze how the success of physical education in strengthening aspects of the Pancasila learner profile towards student character building in one of the elementary schools in Bandung district, West Java. This research uses descriptive qualitative research method with case study design. Participants in this study were Physical Education teachers and grade 5 students. data collection through observation, interviews, and documentation. Data analysis used by researchers is data reduction, data presentation, and data verification. The results showed that physical education learning in one of the elementary schools in Bandung district, West Java had implemented the six aspects of the Pancasila learner profile, namely faith and devotion to God Almighty and noble character, global diversity, independence, mutual cooperation, critical reasoning, and creativity very well. The conclusion in this study shows that the Pancasila learner profile has been successfully implemented in learning PE material for short distance running. All aspects are in line with the results of interviews with physical education teachers and the results of observations of 5th grade students.